2007
DOI: 10.1121/1.2710463
|View full text |Cite
|
Sign up to set email alerts
|

Using cross correlations of turbulent flow-induced ambient vibrations to estimate the structural impulse response. Application to structural health monitoring

Abstract: It has been demonstrated theoretically and experimentally that an estimate of the impulse response (or Green's function) between two receivers can be obtained from the cross correlation of diffuse wave fields at these two receivers in various environments and frequency ranges: ultrasonics, civil engineering, underwater acoustics, and seismology. This result provides a means for structural monitoring using ambient structure-borne noise only, without the use of active sources. This paper presents experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…At the former position of the source, we placed the accelerometer R 0 that was kept fixed all through the experiment. As proposed by Sabra et al (2007), we used the noise generated by a turbulent flow. As a noise source, we employed a dry air blower.…”
Section: B Passive Experimentsmentioning
confidence: 99%
“…At the former position of the source, we placed the accelerometer R 0 that was kept fixed all through the experiment. As proposed by Sabra et al (2007), we used the noise generated by a turbulent flow. As a noise source, we employed a dry air blower.…”
Section: B Passive Experimentsmentioning
confidence: 99%
“…For example, Muto et al (2007) showed numerically how the introduction of fractured welds on three floors of one wall of a finite-element model of a high rise subjected to small-amplitude earthquake excitation gave rise to a new propagating torsional wave. For elastic structures, traveling wave techniques to determine the location and time of occurrence of a high-frequency damage event that has been recorded on a seismic network (Kohler et al, 2009;Heckman et al, 2010) is not very common in the literature, as opposed to passive damage detection methods that do not rely on active sources (e.g., Sabra et al, 2007;Nayeri et al, 2008;Duroux et al, 2010). Snieder and Safak (2006) calculated IRFs by using interferometry on earthquake data from each floor in an instrumented building (the Millikan Library in Pasadena, California).…”
Section: Introductionmentioning
confidence: 99%
“…Noise-correlation (interferometric) methods without active sources have also been tested in laboratory-scale mechanical systems. The impulse response of a metal hydrofoil due to changes in mounting conditions before and after large-amplitude load fluctuations was computed from high-frequency (> 400 Hz) ambient vibration cross correlations (Sabra et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…original ultrasound technique relying on the correlation of non-coherent acoustic fields [13] [14] [15] [16]. Based on passive Green's function reconstruction [17], the principle is that such fields, ordinarily considered as noise in conventional NDT applications, can be judiciously exploited to estimate the response between two measurement points without the need for an active ultrasound source at one of these points.…”
Section: Recent Theoretical and Experimental Work Have Demonstrated mentioning
confidence: 99%